Phylogenomics of Anguis and Pseudopus (Squamata, Anguidae) indicates Balkan-Apennine mitochondrial capture associated with the Messinian event - Gvoždík, Václav; Nečas, Tadeáš; Jablonski, Daniel; Moriarty Lemmon, Emily; Lemmon, Alan R; Jandzik, David; Moravec, Jiří (Molecular phylogenetics and evolution, 2023)
A dated phylogenetic hypothesis on the evolutionary history of the extant taxa of the Western Palearctic lizards Anguis and Pseudopus is revised using genome-wide nuclear DNA and mitogenomes. We found overall concordance between nuclear and mitochondrial DNA phylogenies, with one significant exception - the Apennine A. veronensis. In mitochondrial DNA, this species forms a common clade with the earliest diverging lineage, the southern Balkan endemic A. cephallonica, while it clusters together with A. fragilis in nuclear DNA. The nuclear phylogeny conforms to the morphology, which is relatively similar between A. veronensis and A. fragilis. The most plausible explanation for the mitonuclear discordance is ancient mitochondrial capture from the Balkan ancestor of A. cephallonica to the Apennine population of the A. fragilis-veronensis ancestor. We hypothesize that this capture occurred only in a geographically restricted population. The dating of this presumed mitochondrial introgression and capture coincides with the Messinian event, when the Balkan and Apennine Peninsulas were presumably largely connected. The dated nuclear phylogenomic reconstruction estimated the divergence of A. cephallonica around 12 Mya, while the sister clade representing the A. fragilis species complex consisting of the sister species A. fragilis-A. veronensis and A. colchica-A. graeca further diversified around 7 Mya. The depth of nuclear divergence among the evolutionary lineages of Pseudopus (0.5-1.2 Mya) supports their subspecies status.
Keywords: Phylogeny; mitochondriální DNA; Balkan Peninsula; DNA, Mitochondrial; Lizards; Introgression; ještěři; fylogeneze; Animals; Mitonuclear discordance; Messinian salinity crisis; biologická evoluce; Evolutionary history; Biological Evolution; Slow worm; Glass lizard; zvířata; Balkánský poloostrov